Guest Editorial - Dolly Samson (Higher Learning Research Communications, 2013)
It is an honor and a pleasure to have the December 2013 issue of Higher Learning Research Communications dedicate its issue to selected papers from the 4th International Conference on Teaching and Learning, held in Bangkok in November, 2013. The conference theme, Higher Learning in the ASEAN Context, highlights the emerging community of ten Southeast Asian nations and the upcoming launch of the ASEAN Economic Community (AEC) in 2015. The AEC will affect higher education systems in Southeast Asia in terms of harmonization of higher education and student mobility. This emerging regional demographic gives us a glimpse of the future of transnational education.